محددات نجاح البنك عبر الأنترنت في الجزائر وفق نموذج تقبل التكنولوجيا - ذهبي ريمة; ميهوب سماح (جامعة الوادي University Of Eloued, 2024)
هدفت الدراسة الى استقصاء محددات نجاح استخدام البنك عبر الانترنيت في الجزائر، وفقا لنموذج تقبل التكنولوجيا، من خلال جمع بيانات ومعلومات مستخرجة من 100 استبيان استهدف عملاء بنك بنكسي. وقد توصلت الدراسة الى ان كل من المنفعة المدركة من استخدام البنك عبر الانترنيت وسهولة استخدامه لعبتا دورا أساسيا في تقبل مفهوم البنك عبر الانترنيت في الجزائر، كما ان ثقة المتعاملين ببنك بنكسي ساهمت في تطوير هذا التقبل. This research examines empirically determinants of internet banking success in Algeria, according to the technology acceptance model. A survey was conducted on 100 Banxy customers in order to collect data and information. The results indicated that perceived usefulness and perceived ease of use significantly positively influence acceptance from the users internet banking in Algeria, the results also found that trust in Banxy bank contributed to the development of this acceptance.
Internet banking success in Algeria according to Technology Acceptance Model
Keywords: بنك عبر الانترنت; نموذج تقبل التكنولوجيا; سهولة الاستخدام المدركة; المنفعة المدركة; جزائر